Alkali–silica reaction: Current understanding of the reaction mechanisms and the knowledge gaps. (October 2015) - Rajabipour, Farshad; Giannini, Eric; Dunant, Cyrille; Ideker, Jason H.; Thomas, Michael D.A.
Abstract: Alkali–silica reaction (ASR) is a major concrete durability problem, resulting in significant maintenance and reconstruction costs to concrete infrastructures all over the world. Despite decades of study, the underlying chemical and physical reaction mechanisms remain poorly understood, especially at molecular to micro-scale levels, and this has resulted in the inability to efficiently assess the risk, predict the service life, and mitigate deterioration in ASR-susceptible structures. This paper intends to summarize the current state of understanding and the existing knowledge gaps with respect to reaction mechanisms and the roles of aggregate properties (e.g., composition, mineralogy, size, and surface characteristics), pore solution composition (e.g., pH, alkalis, calcium, aluminum), and exposure conditions (e.g., temperature, humidity) on the rate and magnitude of ASR. In addition, the current state of computer modeling as an alternative or supplement to physical testing for prediction of ASR performance is discussed.